Model of Quality Management Competency for Basic School Directors in Educational Quality Assurance - Kanokphongsathian , Phanchita; Koolnaphadol, Taweesil; Songbundit, Apitee (Rajapark Journal, 2022)
The purposes of this research are as follows: (1) to synthesize the components of quality management competency for basic school directors in educational quality assurance; and (2) to create a model of quality management competency for basic school directors in educational quality assurance. This study employed mixed-method research. The qualitative research methodology was a focus group discussion with 14 key informants, who were selected by purposive sampling method and consisted of educational administrators, educational directors, and teachers responsible for quality assurance in schools. In terms of the quantitative research methodology, the sample group for the quantitative approach consisted of 345 school directors and teachers in schools by determining the sample size using the Rule of Thumb and a multi-stage random sampling method. The research instruments were open-ended questions to guide group discussions and the questionnaires. The statistics used for analyzing the data were content analysis, frequency, percentage, mean, standard deviation, and exploratory factor analysis. The findings of this research were as follows: (1) quality management competency for basic school directors in educational quality assurance consisted of twenty competencies; and (2) The competency factors for the quality management competency for basic school directors in educational quality assurance consisted of five elements: (1) ethical leadership competency (2) conceptual competency (3) quality management process competency (4) organization mobility competency and (5) digital competency.